Mediterranean Modernism
IX, 373 p.
Keywords: This book explores how Modernist movements all across the Mediterranean basin differed from those of other regions. The chapters show how the political and economic turmoil of a period marked by world war, revolution, decolonization, nationalism, and the rapid advance of new technologies compelled artists, writers, and other intellectuals to create a new hybrid Mediterranean Modernist aesthetic which sought to balance the tensions between local and foreign, tradition and innovation, and colonial and postcolonial. .